An innovativefractal architecture model for implementing MapReduce in an open multiprocessing parallel environment - Muslim Mohsin Khudhair; Adil AL-Rammahi; Furkan Rabee (Institute of Advanced Engineering and Science, 2023)
One of the infrastructure applications that cloud computing offers as a service is parallel data processing. MapReduce is a type of parallel processing used more and more by data-intensive applications in cloud computing environments. MapReduce is based on a strategy called